2004
DOI: 10.1165/rcmb.2004-0080oc
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Comparison of Alveolar Macrophages with Monocytes Reveals Distinct Protein Characteristics

Abstract: Alveolar macrophages (AMs) are a subset of tissue macrophages situated in the alveolar milieu. Compared with their precursor blood monocytes, AMs exhibit distinct physiologic functions unique to their anatomic location. However, the molecular details that control monocyte differentiation into AMs remain unknown. This study employed a proteomic approach to define protein characteristics that distinguish AMs from monocytes. AMs and monocytes were obtained from six nonsmoking, healthy donors. Whole cell lysates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…3. Cathepsin D is the most abundant lysosomal protease in differentiated macrophages [84,85]. Activation of cathepsin D allows Mcl-1 to interact preferentially with its E3 ubiquitin ligase, Mcl-1 ubiquitin ligase (Mule, also known as ARF-BP1/ HectH9), rather than with heat shock protein 70 with which it can also interact [34].…”
Section: The Molecular Regulation Of Apoptosis-associated Killingmentioning
confidence: 99%
“…3. Cathepsin D is the most abundant lysosomal protease in differentiated macrophages [84,85]. Activation of cathepsin D allows Mcl-1 to interact preferentially with its E3 ubiquitin ligase, Mcl-1 ubiquitin ligase (Mule, also known as ARF-BP1/ HectH9), rather than with heat shock protein 70 with which it can also interact [34].…”
Section: The Molecular Regulation Of Apoptosis-associated Killingmentioning
confidence: 99%
“…They showed that macrophages are involved in a wide array of biological functions, including cytoskeletal machinery, carbohydrate metabolism, apoptosis, and protein metabolism. Jin et al [143] published a study comparing the proteome of alveolar macrophages and blood monocytes, and showed that blood monocytes displayed higher levels of proteins involved in transcription, metabolism, inflammation, and in control of proteolysis. Preliminary studies of monocyte-derived macrophages from patients with human immunodeficiency virus type 1-associated dementia showed that seven unique protein peaks, between 3 and 20 kDa, were selectively present in samples from patients with dementia [144].…”
Section: Leukocytesmentioning
confidence: 99%
“…LCM with real-time PCR has been successfully used in a limited fashion to study the cytokine gene expression in a murine model of Mtb infection (67). The use of LCM may also facilitate comparative analyses of tissue and circulating blood populations to assess how the peripheral blood compartment reflects local pathogenic processes (68).…”
Section: Lessons Learned and Future Approachesmentioning
confidence: 99%